Amyloidosis cardiomyopathy: update in the diagnosis and treatment of the most common types. (September 2018) - Nativi-Nicolau, Jose; Maurer, Mathew S.
Abstract : Purpose of review: The present article provides an update about the recent advances in the diagnosis and management of the most common types of cardiac amyloidosis, including light chain, wild-type transthyretin (ATTRwt), and mutant transthyretin (ATTRm). Recent findings: The document reviews the utility of diagnostic tools including innovative echocardiographic indices, magnetic resonance T1 mapping and measurement of extracellular volume, and the role and validation of bone scintigraphy for the noninvasive assessment of ATTR amyloidosis. It summarizes the data about therapies for light chain amyloidosis including bortezomib regimens and also novel disease modifying therapies for ATTR amyloidosis such as gene silencers, transthyretin stabilizers, and degraders of amyloid fibrils. Summary: The present review provides the readers with the necessary tools in order to recognize and diagnose cardiac amyloidosis early and introduces the recent advances in management that are improving the outcomes of a condition that was considered to be untreatable.